MANAGEMENT WORK IN THE FIELD OF LOGISTICS IN EU WORLD MARKETS - YEVTUSHENKO, VIKTORIIA; SHUBA, TATIANA; LYASHEVSKA, V.; BOLDYREV, VADIM (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The article considers the problem of improving the efficiency of management work at enterprises operating in the field of logistics in international markets. The efficiency of corporate personnel and successful corporate activities largely depends on the level of competence of employees, which is the most important component of personnel management and compliance with personnel strategy. Today, human resources are considered the most important internal resource to improve production efficiency, so effective personnel management is the key to business success and efficiency. Human resource management involves the formation of "correct" model of employee behavior, so that their qualifications and professionalism meet the requirements of the company, actively initiate and implement their desires in the process. To ensure and improve the skills of managers, rational organization and management should be considered as a prerequisite for effective human resource management, which requires the establishment of new effective methods and forms of selection, placement, evaluation and development of skills. Management of various spheres of public life has its own characteristics, and the study of the management process requires differentiated methods, which is the subject of special research. Management activity is a kind of consciously carried out human activity, the purpose of which is to ensure the effectiveness of work performed (individual or collective), to achieve certain goals, to solve related tasks, to perform functions. The concept of "management" is broader than the concept of "management work", because management activities include management, work, man and nature, in other activities, management activities are leading and guiding. The impact is not in management, but in the process of its implementation. In modern scientific thought, we can identify various methods of defining the concept of managerial work and establish the essence of its category. However, despite the significant contribution of scientists in the study of managerial work, unresolved, in our opinion, remain issues related to the management of managerial work in the field of foreign economic activity of enterprises, including its development in such enterprises.